Which Place for Radical Trial in Genetic Structuralism and in Pragmatic Approach? - Bikbov, Alexander (SocietàMutamentoPolitica, 2021)
The article discusses the use of test / trial as a research tool proposed by different versions of sociology, namely by genetic structuralism owing to Pierre Bourdieu and by pragmatic approach assembled around the work of Luc Boltanski and Laurent Thévenot. The inquiry is contextualized in the author’s study of civic mobilization in Russia taking into consideration sustainability and contingencies of institutional frameworks which shape different types of test. A series of publications produced by both sociological currents and employing the concept of trial is examined in order to retrace its actuation in several research contexts. A special attention is granted to a problem of social structures in which test results are resumed. For this purpose, a more attentive reading is offered to Patrick Champagne’s and Dominique Marchetti’s paper on the affair of ‘contaminated blood’, and to the book by Nicolas Dodier on outcomes of AIDS epidemic. The results let conclude on the compatibility of pragmatic approach with the Foucauldian concept of dispositive, as well as on methodological implications of field theory in study of trials. Making use of examples from Russian protest movement, the article proposes to complete the typology of tests and to account radical tests which target the abnormal reality and the problematic self together with more conventional public trials and controversies mediated by sustainable institutions.